Performance-Informed Budgeting in the U.S. National Government : An Evolutionary Approach and a Work in Progress - Joyce, Philip G. (World Bank, Washington, DC, 2013)
The United States, at the national level of government, has been trying to identify stronger links between performance and funding for at least 50 years. The most recent two presidents had fundamentally different approaches to performance-based reforms. The administration of George W. Bush embraced a top-down, comprehensive approach to performance, embodied by the President's Management Agenda and the Program Assessment Rating Tool (PART). The Obama administration has delegated more of the agenda to the agencies and has abandoned the PART in favor of a more in-depth, targeted approach to evaluation. Continuing challenges in the United States include creating incentives for focusing on the long term rather than the short term, making expanded use of performance information for budget decision making, and simultaneously focusing on performance improvement and reducing unsustainable budget deficits.